2004
DOI: 10.1080/10715760412331273197
|View full text |Cite
|
Sign up to set email alerts
|

Influence of an Orally Effective SOD on Hyperbaric Oxygen-related Cell Damage

Abstract: In a prospective, double-blind, randomised placebocontrolled study, we tested the hypothesis that a new formulation consisting of wheat gliadin chemically combined with a vegetal (thus orally effective) preparation of superoxide dismutase (SOD) allows to prevent hyperbaric oxygen (HBO)-induced oxidative cell stress.Twenty healthy volunteers were exposed to 100% oxygen breathing at 2.5 ATA for a total of 60 min. DNA strand breaks (tail moments) were determined using the alkaline version of the comet assay. Whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
1
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 27 publications
5
54
1
3
Order By: Relevance
“…This is because reactive oxygen species (ROS)-induced DNA base damage leads to the formation of abasic sites during base-excision repair which are detectable in the alkaline Comet assay and MN and NPB in the CBMN Cyt assay are efficiently induced by ROS such as H 2 O 2 , superoxide, and activated neutrophils [Umegaki and Fenech, 2000;Dotan et al, 2004;Muth et al, 2004;Devaraj et al, 2008]. Furthermore, we felt that it was imEnvironmental and Molecular Mutagenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because reactive oxygen species (ROS)-induced DNA base damage leads to the formation of abasic sites during base-excision repair which are detectable in the alkaline Comet assay and MN and NPB in the CBMN Cyt assay are efficiently induced by ROS such as H 2 O 2 , superoxide, and activated neutrophils [Umegaki and Fenech, 2000;Dotan et al, 2004;Muth et al, 2004;Devaraj et al, 2008]. Furthermore, we felt that it was imEnvironmental and Molecular Mutagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Results were mean 6 SEM (>). NS, nonsignificant. portant to use any additional effort and resources to measure other biomarker of oxidative stress such as protein carbonyls and F2-isoprostanes because it is evident that measurement with DNA end-points alone is not sufficient to obtain the full spectrum of ROS-induced damage to the organism [Dotan et al, 2004;Muth et al, 2004;Devaraj et al, 2008]. We did not conduct the challenge assay with ROS because our in vitro studies with human peripheral blood lymphocytes with Se-met, the predominant organic form of selenium, covering both physiological and supraphysiological concentrations, showed no impact on ionizing radiation-induced DNA damage and chromosome aberrations measured using the Comet and the CBMN Cyt assay, respectively [Wu et al, in press].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we showed inflammation-promoted tumour progression was prevented by administration of a SOD derivative, oxykine. Recent reports have verified that oxykine protects cells from hyperbaric oxygeninduced oxidative stress, that is, breaks of DNA strand in healthy volunteers (Muth et al, 2004) and that oxykine prevents oxidative stress-mediated diabetic nephropathy in rodent model of type 2 diabetes (Naito et al, 2005). This orally available molecule will be effective in clinical utilisation to prevent both tumour development and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Given to mice, it exhibited properties similar to Protandim (Vouldoukis et al, 2004 b) leading up to a fourfold increase of circulating and hepatic tissue antioxidant enzyme activities. In healthy volunteers, oral Glisodin® was associated with less lipid peroxidation (Muth et al, 2004). Very recently, these authors demonstrated that a pre-treatment with Glisodin® may be a therapeutic option to reduce oxidative cell injury affiliated with aortic cross-clamping in pigs (Kick et al, 2007).…”
Section: Melon Juice Extract Rich In Superoxide Dismutase Activitymentioning
confidence: 95%